New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae) - Bocek, Matej; Adamkova, Kristyna (Zootaxa, 2019)
The Moluccan net-winged beetle fauna remains poorly studied and here, new species of Schizotrichalus Kleine, 1926 and Eniclases Waterhouse, 1879 are reported from Halmahera. Using morphological traits and cox1 mitochondrial DNA sequences, we propose two new species, Eniclases kusyi sp. nov. and Schizotrichalus halmaherensis sp. nov., and redescribe E. moluccanus Kleine, 1930. New molecular data confirm morphology-based sister relationships between Schizotrichalus and Eniclases and the analysis identifies the combined area of the present-day Halmahera and New Guinea as an ancestral area of these genera. Now, Halmahera and New Guinea are quite similar in respect of the number of trichaline genera. Concerning the size of islands and the recent origin of the nowadays northern Moluccas, these results are unexpected and thus the general validity of this distribution pattern should be confirmed with other groups of beetles.